Pengaruh Penambahan Konsentrasi Saccaromyces Cerevisiae Terhadap Produksi Bioetanol Dari Limbah Biomassa Pelepah Sawit - Maya Ratna Sari; David Andrio; Sri Rezeki Muria (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Oil palm frond juice (OPFJ) has the potential as a promising bioethanol forming substrate because of the simple high sugar composition with a total COD content of 36.364 g / L. In this study, the microorganisms used were S. cerevisiae, the best fungi for bioethanol fermentation This study aims to determine the effect of inoculum concentration of S. cerevisae on the fermentation of the oil palm frond juice (OPFJ) for the process of bioethanol formation, allowance for COD, formation for Volatile Suspended Solid (VSS).The study was conducted using 250 ml erlenmeyer with a working volume of 150 ml with a ratio of S.cerevisae as much as 10%; 20%; 30% and 40% (v/v) with a OPFJ substrate content; 90%; 80%: 70% and 60% (v/v) at 100 rpm for 72 hours. Based on the results of the study, the highest efficiency of COD dissolved as a 50%, respectively. VSS growth is 168 m/L/hour with efficiency of growth is 41% through Reactor R1 (S.cerevisiae: Substrate = 30:70). It produces the highest bioethanol formation with the 10 % addition of S. cerevisiae (v/v) of 25,42 mg/L with the efficiency of bioethanol formation is 83% with stirring 100 rpm at 48 hours.Keywords : Fermentation, Bioethanol, Juice Oil Palm Fronds, Saccaromyces cerevisiae